Incorrect use of medicines by patients post cerebrovascular accident - Dopico da Silva, Lolita; de Mendonça Henrique, Danielle (Investigación y Educación en Enfermería, 2025)
Objective. To evaluate how patients cerebrovascular accidents (CVA) victims use their medicines at home. Methodology. Cross sectional study. A representative sample of 30 patients who received home care in the city of Rio de Janeiro (Brazil) in 2008 was studied. Information about CVA risk factors and the medicines they were taking was collected using a structured interview to the patients, and the DRUGDEX® classification system was used to determine the correct or incorrect use of the medicines. Results. Participants were mostly elder women. The average of medicines per patient was of 3.3 medicines. The main reasons for mistaking were: taking medicines with food, and taking other medicines at the same time. The highest proportions of incorrect administration of medicines in more than 50% of the doses were: Spironolactone, glibenclamide, and atenolol (each of them with a 100.0%), simvastatin (87.5%), captopril (72.5%) and NPH insulin (66.7%). Conclusion. A great proportion of patients after having suffered a CVA use their medicines prescribed for home treatment incorrectly.